Exploring the development of inventory asset management system (IAMS) - Mohd Zaid, Che Maliki Che; Mohamad Rosman, Mohamad Rahimi; Mat Nawi, Nur Ainatul Mardiah; Ahmad, Awais Karni (International Journal of Accounting, Finance and Business, 2026)
Asset inventory and management help organizations efficiently track, manage, and maintain physical assets such as equipment, electronics, and furniture. However, currently, many organizations are still using manual recordkeeping to manage their assets. Thus, this paper explores the development of a computerised asset management and inventory system (IAMS). The proposed system is built using Laravel and MySQL; the system replaces outdated manual and spreadsheet-based methods with a unified digital platform that has role-based access for Staff, Technicians, and Administrators. The main functionalities of this system include asset registration with various details or information, movement tracking for borrowings and returns, maintenance logging with condition updates, approval workflows, and automated reporting. The system strengthens user accountability, reduces asset loss, supports preventive maintenance, and provides real-time visibility into asset status. Although fully functional, future enhancements such as barcode scanning, mobile accessibility, and other system improvements are recommended to make it usable for a longer time.